Case Report: Adolescent With Autism and Gender Dysphoria - Zupanič, Sanja; Kruljac, Ivona; Šoštarič Zvonar, Mojca; Drobnič Radobuljac, Maja (Frontiers in Psychiatry, 2021)
There is increasing clinical evidence of an association between gender variability, gender dysphoria (GD) and autism spectrum disorder (ASD). This seems to be a two-way relationship, a person with GD is more likely to be diagnosed with ASD and vice versa. In youth, it is important to distinguish whether the presented symptoms are a manifestation of ASD focus on special interests or symptoms of co-occurring GD. This distinction is crucial in the process of planning reversible and especially irreversible medical procedures in the context of treatment. We present the case of a birth-assigned female adolescent with GD, who enrolled in our clinic at the age of 16.5 years with “being transgender” as her main complaint accompanied by a wish for surgical breast removal. His (as the patient prefers to use male pronouns) medical and developmental history involved obesity, hyperlipidemia, delays in social and language development and specific interests and rituals. He presented with half a year of untreated depression, suicidal thoughts and non-suicidal self-injuring, social phobia and relative social isolation. Comprehensive clinical assessments revealed a female karyotype (46, XX), normal female genitalia and unremarkable hormonal status. Clinical psychological assessments reported GD, ASD with average intellectual abilities and co-occurring symptoms of depression and anxiety. Other disorders, such as psychosis, personality disorder and dysmorphophobia, were excluded during longer-term diagnostic and psychotherapeutic processes. Our first aim was to build a good therapeutic alliance with the patient and treat depression and suicidality. He refused to take sertraline, but took a St. John’s Wort over-the-counter peroral preparation in the form of infusions. His mood improved, he was no longer suicidal and started social transitioning, yet he remained socially phobic. At the time of writing, he is 20 years old, waiting for bilateral mastectomy and receiving regular triptorelin depot and testosterone depot intramuscular injections. Even though the diagnostic procedures and transition process in autistic gender diverse adolescents may take longer than in non-autistic individuals, ASD is not a contraindication to the gender transition process. We present a well-documented case of a slow social and medical transition resulting in gradual improvement of co-occurring symptoms of GD.